2017
DOI: 10.1002/2211-5463.12341
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine and histidine residues are involved in Escherichia coli Tn21 MerE methylmercury transport

Abstract: Bacterial resistance to mercury compounds (mercurials) is mediated by proteins encoded by mercury resistance ( mer ) operons. Six merE variants with site‐directed mutations were constructed to investigate the roles of the cysteine and histidine residues in MerE protein during mercurial transport. By comparison of mercurial uptake by the cell with intact and/or variant MerE, we showed that the cysteine pair in the first transmembrane domain was critical for the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The mercuric reductase MerA is the central enzyme in the microbial mercury detoxification system and merA is a suitable biomarker for examining the functional diversity of Hg detoxification ( Boyd and Barkay, 2012 ). The merE gene is a predicted small ORF immediately following merD in many Gram-negative mer operon sequences, and it is proposed to encode a transporter of Hg 2+ or methylmercury ( Sone et al, 2017 ). MerF could transport ionic mercury from the periplasmic protein MerP across the bilayer to MerA and it plays a similar function as that of MerT ( Barkay et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mercuric reductase MerA is the central enzyme in the microbial mercury detoxification system and merA is a suitable biomarker for examining the functional diversity of Hg detoxification ( Boyd and Barkay, 2012 ). The merE gene is a predicted small ORF immediately following merD in many Gram-negative mer operon sequences, and it is proposed to encode a transporter of Hg 2+ or methylmercury ( Sone et al, 2017 ). MerF could transport ionic mercury from the periplasmic protein MerP across the bilayer to MerA and it plays a similar function as that of MerT ( Barkay et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the application of this process has been made easier by the transgenic approach (Saravanan et al, 2022). For example, Hg‐declining bacterial strains of Escherichia coli have been modified by mer operon clone establishment and other recombinant DNA methods for bioremediation (Maqsood et al, 2022; Rafeeq et al, 2023; Sone et al, 2017).…”
Section: Microbial Bioremediationmentioning
confidence: 99%
“…In addition to MerT, other mercury transporters identified in mercury-resistant bacteria include MerC, MerE, and MerF. We have previously shown that MerE is a mercury transporter and transports Hg 2+ and MeHg, [38][39][40] and MerT transports phenylmercury. 32,41) However, the functions of these transporters remained unclear.…”
Section: Molecular Mechanisms Of Mercurial Resistance In Pseudomonas ...mentioning
confidence: 99%